Templating of carbon in zeolites under pressure: synthesis of pelletized zeolite templated carbons with improved porosity and packing density for superior gas (CO2 and H2) uptake properties - Balahmar, Norah; Lowbridge, Alexander M.; Mokaya, Robert (Royal Society of Chemistry, 2016)
This report explores the use of compacted zeolite pellets as templates for the preparation of pelletized zeolite templated carbons (ZTCs). The effects of zeolite compaction before use as hard templates were investigated through the compression of powder forms of zeolites at 370 MPa or 740 MPa prior to their use as templates. The resulting carbon samples were compared to compacted conventionally templated (with powdered zeolites) ZTC. The use of compacted zeolite pellets results in pelletized ZTCs that simultaneously exhibit higher porosity and higher packing density, which translates to highly enhanced volumetric gas (CO2 and hydrogen) uptake. For CVD-derived samples, the pelletized ZTCs achieve 10% higher surface area than powdered samples (and reach > 2000 m2 g-1) despite their packing density increasing from ca. 0.55 to 0.85 g cm-3, which means that the surface area per unit volume increases by ca. 60% from between 1000 and 1100 m2 cm-3 for the powdered ZTCs to ca. 1670 m2 cm-3 for pelletized samples. Thus their volumetric CO2 uptake at 25 oC increases by 140% and 85% at 1 and 20 bar, respectively, compared to powdered ZTCs. Pelletized ZTCs prepared via a combination of liquid impregnation and CVD achieve much higher surface area of 3000 m2 g-1 (compared to 2700 m2 g-1 for powder samples) despite an increase in packing density from 0.44 to 0.69 g cm-3, resulting in a surface area per unit volume rise of 75% from 1189 m2 cm-3 to 2085 m2 cm-3. The high surface area pelletized ZTCs have attractive gravimetric hydrogen uptake of 6.6 wt% (5.5 wt% for powdered sample) at 20 bar and -196 oC, and reach volumetric hydrogen storage capacity of 46 g l-1 (24 g l-1 for powder sample). For CO2 uptake at 25 oC and at 20 bar, the volumetric uptake of the high surface area pelletized ZTC is nearly twice that of the powdered sample; 668 g l-1 compared to 360 g l-1.